2007
DOI: 10.4049/jimmunol.178.6.3918
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of C1 and C2 Epitopes for Hemopoietic Stem Cell Transplantation: Role for Sequential Acquisition of HLA-C-Specific Inhibitory Killer Ig-Like Receptor

Abstract: Killer Ig-like receptors (KIR) and HLA class I ligands were studied in unrelated hemopoietic stem cell transplantation for chronic myeloid leukemia (n = 108). Significantly improved overall survival was observed in patients, which were homozygous for HLA-C-encoded group 1 (C1) ligands compared with those with group 2 (C2) ligands. Favorable outcome in the former patient group was an early effect that was highly significant in patients transplanted with G-CSF-mobilized peripheral blood and patients with advance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
62
2
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 28 publications
11
62
2
3
Order By: Relevance
“…13 When the analyses were performed according to the 'missing ligand' concept, Miller et al 26 reported that, similar to our findings, early CML patients were at higher risk of aGVHD (III-IV). Other reports, however, showed no association of missing ligands with aGVHD after HLA identical sibling transplantation, neither with unmanipulated 27,28 nor with TCD grafts.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…13 When the analyses were performed according to the 'missing ligand' concept, Miller et al 26 reported that, similar to our findings, early CML patients were at higher risk of aGVHD (III-IV). Other reports, however, showed no association of missing ligands with aGVHD after HLA identical sibling transplantation, neither with unmanipulated 27,28 nor with TCD grafts.…”
Section: Discussionsupporting
confidence: 78%
“…Concordant with the 'missing ligand' model, decreased survival of HLA-C2C2 CML patients was attributed to the delayed reconstitution of inhibitory KIR2DL1 receptors on NK cells post transplant, and hence their inability to kill cells with downregulated HLA-C2C2 ligands in a timely manner. 13 Also, the analyses of the activating KIR receptors showed donors' KIR2DS2 to be a significant risk factor for overall survival (OS) of myeloid leukemia HLA-C2C2 patients. 14 In addition, not only individual genes but also KIR haplotypes of donors were associated with an increased risk of acute GVHD (aGVHD), higher relapse rates and worse OS of HLA-C1C1 patients diagnosed with myeloid diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in vitro NK cell activation and expansion to obtain higher doses of possibly more effective cell populations need to be studied. 26,27 Some single-center experiences showed a benefit of IL-2-stimulated NK cells compared with freshly isolated, resting NK cells with regard to the cytotoxicity against leukemic and tumor targets. 18,[28][29][30][31] This was due to a strong upregulation of the activating receptors NKp30, NKp44, NKp46 and NKG2D during IL-2 stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies were compatible with the missing KIR ligand model. 3,5,[15][16][17][18] However, others did not reveal a benefit of missing KIR ligands, 13,19,20 or even showed an adverse effect, particularly in C2/2 recipients. 12,14,21,22 In T cell replete, non-antithymocyte globulin (ATG)-based sibling PBSCT, we have recently reported a superior OS and PFS in C1/2 heterozygous recipients compared with C2/2 recipients, 21 a finding diametrically opposed to the missing KIR ligand model.…”
Section: Introductionmentioning
confidence: 99%
“…As most Caucasians possess a full complement of inhibitory KIRs, 11 the missing KIR ligand model has been suggested an acceptable surrogate for the receptor-ligand model, having the advantage that donor KIR typing is not required. 3,[12][13][14] In this way, a series of studies have addressed the role of missing KIR ligands in HSCT, but reached partly divergent results. Several studies were compatible with the missing KIR ligand model.…”
Section: Introductionmentioning
confidence: 99%